Pemberdayaan Karang Taruna dan Remaja Masjid melalui Kegiatan Sosial Keagamaan - Ruslan (Communautaire: Journal of Community Service, 2023)
The existence of youth organizations such as youth groups and mosque youth basically functions to carry out coaching for the younger generation, especially with relevant activities. But in reality the two youth organizations above are often unable to carry out their functions and roles properly. So it is not strange if in the end the two containers become suspended animation. This paper attempts to describe the implementation of youth and mosque empowerment activities through social-religious activities in Errabu village. This community empowerment activity is carried out using the Participatory Action Research (PAR) approach which aims to raise awareness and empower them to identify social problems and potential as well as carry out community interventions in the context of community empowerment. The results of the activity showed that the youth and mosque empowerment activities were carried out in 3 stages, namely the identification stage, preparation of activity plans, and program implementation.